Therapeutic Targets in Allergic Conjunctivitis - Bisant A. Labib; DeGaulle I. Chigbu (MDPI AG, 2022)
Allergic conjunctivitis (AC) is a common condition resulting from exposure to allergens such as pollen, animal dander, or mold. It is typically mediated by allergen-induced crosslinking of immunoglobulin E attached to receptors on primed conjunctival mast cells, which results in mast cell degranulation and histamine release, as well as the release of lipid mediators, cytokines, and chemokines. The clinical result is conjunctival hyperemia, tearing, intense itching, and chemosis. Refractory and chronic cases can result in ocular surface complications that may be vision threatening. Patients who experience even mild forms of this disease report an impact on their quality of life. Current treatment options range from non-pharmacologic therapies to ocular and systemic options. However, to adequately control AC, the use of multiple agents is often required. As such, a precise understanding of the immune mechanisms responsible for this ocular surface inflammation is needed to support ongoing research for potential therapeutic targets such as chemokine receptors, cytokine receptors, non-receptor tyrosine kinases, and integrins. This review utilized several published articles regarding the current therapeutic options to treat AC, as well as the pathological and immune mechanisms relevant to AC. This review will also focus on cellular and molecular targets in AC, with particular emphasis on potential therapeutic agents that can attenuate the pathology and immune mechanisms driven by cells, receptors, and molecules that participate in the immunopathogenesis and immunopathology of AC.